DINAMIKA KELOMPOK SEPARATIS DONBAS: IMPLIKASI TERHADAP ESKALASI KONFLIK RUSIA-UKRAINA - Prastri Kamurahang; Imam Mahdi (Indonesian Journal of International Relations, 2025)
This study analyzes the dynamics of separatist groups in the Donbas region, influenced by ethnic and linguistic factors, and their implications for the escalation of the Russia-Ukraine conflict. Using a qualitative approach and desk research within a neorealist theoretical framework, this study explores how Russia's military, economic, and political support transformed these separatists into effective actors. This also forms part of Russia's geopolitical strategy against NATO and EU expansion. Donbas separatist groups function as Russia's proxies and political tools, creating a conflict zone that prolongs regional instability. This support exacerbates tensions and hinders diplomatic efforts. This research concludes that Donbas separatists are geopolitical instruments significantly prolonging the conflict, impeding peaceful resolution, and worsening Russia's relations with the West